Clinical Implications for Children Developing Direct Hyperbilirubinemia on Extracorporeal Membrane Oxygenation. Issue 3 (March 2022) - Alexander, Erin; O'Sullivan, Donnchadh; Aganga, Devon; Hassan, Sara; Ibrahim, Samar H.; Absah, Imad
ABSTRACT: Objective: Extracorporeal membrane oxygenation (ECMO)-associated direct hyperbilirubinemia (DHB) is likely multifactorial. The objective of this study is to assess the frequency and risk factors for developing direct hyperbilirubinemia while on ECMO, and its implication on the mortality of children. Methods: We performed a retrospective study between January 2010 and January 2020. Using Mayo Clinic electronic health record, we identified children (<18 years) who required veno-arterial (VA) ECMO support. Demographics, ECMO indication, laboratory findings, and outcomes were abstracted. Illness acuity scores, including vasoactive-ionotropic score (VIS), were used to assess disease severity at time of admission. Study cohort was divided into two groups: children who developed direct hyperbilirubinemia (DHB) on ECMO and children who did not (control). DHB was defined as direct bilirubin (DB) of >1.0 mg/dL. Disease acuity and mortality rates were compared between the two groups. Logistic regression was used to analyze the risk of mortality independent of potential confounding variables. Results: We identified 106 children who required ECMO support during the study period. Of those, 36 (34%) children developed DHB on ECMO. Illness acuity scores were significantly higher in the DHB group on ECMO day 2 ( P = 0.046) and day 7 ( P = 0.01). Mortality rate was higher in the DHB group 72%, versus 29% in the control group ( P < 0.001). Conclusion: DHB was associated with a higher mortality rate than the control group.